CORRELATION BETWEEN KNOWLEDGE AND SELF-REPORTED PRACTICE REGARDING CENTRAL LINE-ASSOCIATED BLOODSTREAM INFECTION PREVENTION AMONG NURSES AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2026)
Introduction: Central Line-Associated Bloodstream Infection (CLABSI) is one of the most serious healthcare-associated infections, increasing mortality rates, duration of hospital stays, and treatment costs. Assessing the knowledge and self-reported practice of nurses helps identify gaps, thereby enhancing their role and the quality of care in CLABSI prevention.Objective: To determine the prevalence of knowledge and self-reported practice regarding CLABSI prevention and the correlation between them among nurses at Military Hospital 175Materials and Methods: A descriptive cross-sectional study was conducted on 91 nurses working at Military Hospital 175. The questionnaire covered personal characteristics, knowledge, and self-reported practices related to CLABSI prevention. Data were processed using SPSS software. Descriptive statistics were used to present frequencies and percentages, while Spearman correlation analysis was employed to determine the relationship between knowledge and self-reported practiceResults: The rate of nurses with correct self-reported practice regarding CLABSI prevention was 90.1%, while the rate of adequate knowledge was 75.8%. Knowledge in some areas remained limited, particularly concerning dressing change intervals and catheter care. Correlation analysis showed that knowledge had a moderate positive correlation with nurses' CLABSI prevention self-reported practices (r = 0.46; p < 0.001)Conclusion: Nurses at Military Hospital 175 demonstrated a relatively high rate of correct self-reported practice in CLABSI prevention; however, knowledge in certain areas remains limited. There is a positive correlation between knowledge and CLABSI prevention self-reported practice.
Keywords: CLABSI; nursing; knowledge; self-reported practice; infection prevention.